SITUS-SITUS KEAGAMAAN DI PALEMBANG: SUATU TINJAUAN KAWASAN - Retno Purwanti; Eka Asih Putrina Taim (BRIN, 1995)
The name Palembang began to appear in Indonesian archaeological records, starting from the discovery of Old Malay and Pallawa script inscriptions. The periodization of these inscriptions is Â± 7th century AD. Since then, attention to the antiquity of this area has been given by experts with an interest in the field of ancient Indonesian history. Shnitger, Westenenk, Coedes are examples of enthusiasts who have had considerable interest in the relics of this area.